2020
DOI: 10.1371/journal.pone.0241984
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum Beta-lactamase and AmpC beta-lactamases producing gram negative bacilli isolated from clinical specimens at International Clinical Laboratories, Addis Ababa, Ethiopia

Abstract: Background Extended spectrum Beta-lactamases (ESBLs) and AmpC beta-lactamases (AmpC) are the common enzymes produced by gram negative bacilli, which are their main mechanisms of resistance to all generations of cephalosporins. Hence, this study aimed to determine the magnitude of ESBLs and AmpC producing gram negative bacilli (GNB) isolated from clinical specimens at International clinical Laboratories in Addis Ababa, Ethiopia. Methods A cross sectional study was conducted from January to May 2018. From diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 45 publications
6
31
3
Order By: Relevance
“…The antimicrobial investigations from this study showed E. coli clinical isolates to have the highest resistance to cefepime, followed by amikacin and piperacillin/tazobactam, but was highly susceptible to trimethoprim/sulfamethoxazole and meropenem. This observation is in contrast to what was recently observed in Ethiopia by Tekele et al [35] where E. coli (from various clinical specimens such as urine, pus, body fluids, sputum, stool, ear and eye discharges) showed the highest resistance to ampicillin followed by amoxicillin with clavulanic acid. Also, although E. coli isolates from this study showed the highest resistance to cefepime, followed by amikacin, a study by Yılmaz et al [36] showed to E. coli (from urinary tract infections) as having the highest resistance to ampicillin.…”
Section: Discussioncontrasting
confidence: 99%
“…The antimicrobial investigations from this study showed E. coli clinical isolates to have the highest resistance to cefepime, followed by amikacin and piperacillin/tazobactam, but was highly susceptible to trimethoprim/sulfamethoxazole and meropenem. This observation is in contrast to what was recently observed in Ethiopia by Tekele et al [35] where E. coli (from various clinical specimens such as urine, pus, body fluids, sputum, stool, ear and eye discharges) showed the highest resistance to ampicillin followed by amoxicillin with clavulanic acid. Also, although E. coli isolates from this study showed the highest resistance to cefepime, followed by amikacin, a study by Yılmaz et al [36] showed to E. coli (from urinary tract infections) as having the highest resistance to ampicillin.…”
Section: Discussioncontrasting
confidence: 99%
“…As shown in Figure 1 , AmpC producers exhibited significantly higher resistance rates than AmpC-negative strains. This observation extensively corroborated the findings of previous authors, associating AmpC production with increasing resistance to diverse antimicrobial classes [ 16 18 ]. Antimicrobial resistance is linked to the increasing spread of MDR strains, and since infections caused by these organisms are extremely difficult to treat, recognition and awareness of their prevalence in the community are crucial [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…ESBL has the ability to confer bacterial resistance to penicillin; first-, second-and thirdgeneration cephalosporins; and aztreonam (but not the cephamycins or carbapenems) by hydrolysis of these antimicrobials, and which are inhibited by β-lactamase inhibitors such as clavulanic acid. [7][8][9][10] ESBL was first identified in 1983. Within a short span of time ESBL has evolved drastically with over 300 variants being detected in different members of the family Enterobacteriaceae and other nonenteric organisms.…”
Section: Mdr Is Commonly Seen In Methicillin Resistantmentioning
confidence: 99%
“…ESBL was differentiated from Amp C-type β-lactamases, when the isolates were resistant to cephalosporins but sensitive to clavulanic acid in combination with cephalosporins and are resistant to carbapenem. [7][8][9]…”
Section: Antimicrobial Sensitivity Testingmentioning
confidence: 99%